2014
DOI: 10.1371/journal.pone.0104192
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chitosan on Intestinal Inflammation in Weaned Pigs Challenged by Enterotoxigenic Escherichia coli

Abstract: The aim of this study was to investigate whether supplementation with chitosan (COS) could reduce diarrhea and to explore how COS alleviates intestinal inflammation in weaned pigs. Thirty pigs (Duroc×Landrace×Yorkshire, initial BW of 5.65±0.27) weaned at age 21 d were challenged with enterotoxigenic Escherichia coli during a preliminary trial period, and then divided into three treatment groups. Pigs in individual pens were fed a corn-soybean meal diet, that contained either 0 (control), 50 mg/kg chlortetracyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 32 publications
1
62
1
Order By: Relevance
“…Chitosan as a dietary supplement has been explored for its potential as an antimicrobial growth promoter and has been shown to promote growth in broiler chickens [12, 13] and pigs [14]. This could be ascribed to higher feed intake, serum growth hormone, and IGF-1 concentrations [15].…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan as a dietary supplement has been explored for its potential as an antimicrobial growth promoter and has been shown to promote growth in broiler chickens [12, 13] and pigs [14]. This could be ascribed to higher feed intake, serum growth hormone, and IGF-1 concentrations [15].…”
Section: Discussionmentioning
confidence: 99%
“…The lesion score average, intestinal morphometry, goblet cell numbers, and inflammatory cells were used in the statistical analysis with 30 fields per segment and Chitooligosaccharide for piglets: effects on performance, viscera and intestinal morphometry (HAN et al, 2007;XU et al, 2013;WANG et al, 2012), with good results right after weaning. This pronounced effect for piglet growth seems to be related the ability of COS to act as a selective agent for gut bacteria, inhibiting the proliferation of noxious bacteria such as E. coli or Bacillus cereus (HAN et al, 2007;KUMAR et al, 2007;XIAO et al, 2014). This may be favorable for performance due to a reduction in the incidence of diarrhea (HAN et al, 2007;XU et al, 2013;WANG et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Xiao et al (2014) identified a mechanism of immune regulation related to the use of 300 ppm COS in weaning piglet feed associated 1 2 jejunum) and Peyer's patches (ileum) (HERDT, 1999). A cubic epithelium and villi fusion interfere with the absorptive function of these segments and could lead to slower body growth in piglets.…”
Section: Crypt (µMmentioning
confidence: 99%
“…Chitosan is derived from chitin. The immune responses of pigs [6], mice [7], rats [8], and fish [9] have been modulated by chitosan. T cells and other immune cells produce cytokines, which are essential to the immune response.…”
Section: Introductionmentioning
confidence: 99%